2022
DOI: 10.1093/beheco/arab147
|View full text |Cite
|
Sign up to set email alerts
|

Spatial personalities: a meta-analysis of consistent individual differences in spatial behavior

Abstract: Individual variation in behavior, particularly consistent among-individual differences (i.e., personality), has important ecological and evolutionary implications for population and community dynamics, trait divergence, and patterns of speciation. Nevertheless, individual variation in spatial behaviors, such as home range behavior, movement characteristics, or habitat use has yet to be incorporated into the concepts or methodologies of ecology and evolutionary biology. To evaluate evidence for the existence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 105 publications
3
55
3
Order By: Relevance
“…While it is logical that researchers explicitly study or control for the effects of the environment (including other individuals), we would have expected to find an increase in the study of the internal state, motion, and navigation, as well as in the percentage of studies addressing other components of the MEF in combination with external factors. Research on internal state showed a small growth over the years, which could be due to an increase in the number of studies investigating the links between energetic conditions and behavior within tracks [ 21 ], or the increase in the studies examining the links between individual behavioral type (i.e personality) and movement [ 62 ]. Thus, the technological improvements have not been sufficiently exploited.…”
Section: Discussionmentioning
confidence: 99%
“…While it is logical that researchers explicitly study or control for the effects of the environment (including other individuals), we would have expected to find an increase in the study of the internal state, motion, and navigation, as well as in the percentage of studies addressing other components of the MEF in combination with external factors. Research on internal state showed a small growth over the years, which could be due to an increase in the number of studies investigating the links between energetic conditions and behavior within tracks [ 21 ], or the increase in the studies examining the links between individual behavioral type (i.e personality) and movement [ 62 ]. Thus, the technological improvements have not been sufficiently exploited.…”
Section: Discussionmentioning
confidence: 99%
“…This two-way relationship between habitat and hormones may drive a positive feedback loop that reinforces habitat selection behaviour. With emerging evidence habitat selection behaviour is indeed repeatable (Stuber et al, 2022), and that continuous adult exposure to stressors can epigenetically alter offspring hormonal responses to the same stressors (Brass et al 2020), do intergenerational glucocorticoid-habitat selection feedback loops underlie specialization of populations on habitats? Looking beyond populations, an integrated approach to studying glucocorticoids and habitat selection may also provide insights into ecosystem functioning and the ability of species to respond to environmental change. The carbon stress hypothesis (Hawlena and Schmitz 2010) purports animals facing predation stress have higher cellular respiration rates, making them carbon limited.…”
Section: Box 2 – Future Directionsmentioning
confidence: 99%
“…This two-way relationship between habitat and hormones may drive a positive feedback loop that reinforces habitat selection behaviour. With emerging evidence habitat selection behaviour is indeed repeatable (Stuber et al, 2022), and that continuous adult exposure to stressors can epigenetically alter offspring hormonal responses to the same stressors (Brass et al 2020), do intergenerational glucocorticoid-habitat selection feedback loops underlie specialization of populations on habitats?…”
Section: Box 2 – Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in behavioral ecology have long-established the framework and tools to quantify consistency in individual behaviors, and the existence of animal personalities (aka temperament or behavioral types; hereafter BTs) in traits such as boldness, exploration and sociability [13,14]. More recently, accumulating evidence demonstrates that individuals are also repeatable in their movement and spatial behaviors, forming "spatial-BTs" [10,15]. Examples include repeatable home range behaviors [16,17], habitat use [18,19], or ner scale movement indices like maximal daily displacement [20,21].…”
Section: Introductionmentioning
confidence: 99%